Iljinskaea (Brassicaceae), a new genus based on Conringia planisiliqua - Al-Shehbaz, Ihsan A.; Özüdoğru, Bariş; German, Dmitry A. (Phytotaxa, 2021)
Iljinskaea is described as a new monospecific genus based on a critical evaluation of morphology and in light of the extensive molecular phylogenetic data. The new combination I. planisiliqua is proposed, and the distinguishing characters separating the new genus from Conringia are discussed. The new tribal assignment of Iljinskaea in the Isatideae is discussed and compared with the previous placement in the Conringieae.